New Antibiotics Against Multidrug-Resistant Gram-Negative Bacteria in Liver Transplantation: Clinical Perspectives, Toxicity, and PK/PD Properties - Andrea Lombardi; Andrea Lombardi; Laura Alagna; Emanuele Palomba; Giulia Viero; Anna Tonizzo; Davide Mangioni; Davide Mangioni; Alessandra Bandera; Alessandra Bandera (Transplant International, 2024)
Antimicrobial resistance is a growing global health problem, and it is especially relevant among liver transplant recipients where infections, particularly when caused by microorganisms with a difficult-to-treat profile, are a significant cause of morbidity and mortality. We provide here a complete dissection of the antibiotics active against multidrug-resistant Gram-negative bacteria approved over the last years, focusing on their activity spectrum, toxicity profile and PK/PD properties, including therapeutic drug monitoring, in the setting of liver transplantation. Specifically, the following drugs are presented: ceftolozane/tazobactam, ceftazidime/avibactam, meropenem/vaborbactam, imipenem/relebactam, cefiderocol, and eravacycline. Overall, studies on the safety and optimal employment of these drugs in liver transplant recipients are limited and especially needed. Nevertheless, these pharmaceuticals have undeniably enhanced therapeutic options for infected liver transplant recipients.